NEW TRENDS IN SHAPING TOURISM PRODUCTS - Meyer, Beata (Acta Scientiarum Polonorum. Oeconomia, 2010)
The process of tourist products development should be treated multidimensional because of numerous internal and external factors and actors involved. Tourism products are created primarily by tourist enterprises and tourist regions, which on one hand respond to the tourism demands and on the other hand, create tourist products based on their own objectives. When tourist regions are being considered, internal factors are of big importance among determinants infl uencing the process of building a tourism product. In case of tourist enterprises the most important determinants can be traced in the number of incoming tourists and their diverse needs. One of the new trends that gain importance globally is the concept of sustainable development which helps to protect environmental values, sets limits for the development of tourism products and at the same time increases tourist attractiveness of an area.